IN SILICO DOCKING STUDIES ON THE COMPONENTS OF INONOTUS SP., A MEDICINAL MUSHROOM AGAINST CYCLOOXYGENASE-2 ENZYME - SETTI SUDHARSAN MEENAMBIGA; Rajagopal, Kalyanaraman; R, Durga (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Inonotus sp., mushroom is widely present and known for its medicinal property. This mushroom produces several bioactive compounds with various pharmaceutical uses. In the present study, about 8 biologically active compounds from Inonotus sp., were analyzed for its drug likeliness based on Lipinski's rule of five and inhibitor property against the COX-2 enzyme, a protein responsible for inflammation. The compounds which satisfy the Lipinski's rule namely inotilone, 4-(3,4-dihydroxyphenyl)butanone and hispidin were subjected to docking experiments using AutoDock 4.2. Molecular docking studies revealed that inotilone, hispidin and 4-(3,4-dihydroxyphenyl) buanone bind effectively to the active site region of COX-2 with a binding energy of -6.73, -7.78 and -5.63 respectively. Hence, compounds reported from Inonotus sp., were found to possess potential medicinal value with anti-inflammatory properties and this provides potential insight to develop new COX-2 inhibitors. Keywords Inonotus sp., Inflammation, COX-2, AutoDock.